FORMULA FOR CALCULATION OF MAGNETIC FIELD STRENGTH OVER THE MIDDLE OF THE GAP OF A BIPOLAR SUSPENDED IRON SEPARATOR - Zagirnyak, Mykhaylo (Journal of Energy Technology, 2024)
A formula providing the possibility of calculating with sufficient accuracy the strength of the magnetic field over the middle of the inter-polar gap formed by sloping surfaces of pole pieces of U-typeelectromagnets of suspended iron separators is presented.